2016
DOI: 10.1016/j.rbre.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia in systemic lupus erythematosus: is it associated with the neuropsychiatric manifestations of the disease?

Abstract: Hyperuricemia in SLE patients is independently associated with the occurrence of stroke and peripheral neuropathy. It is also independently associated with hypertension, hyperlipidemia, and history of arterial thrombosis, which are the major stroke and myocardial infarction risk factors in SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Because early intervention on LN improves long-term survival and kidney damage [11], it is important to predict renal damage early. The prevalence of hyperuricemia in SLE patients is reported to be approximately 16.1% [12] and 29% [13]. In LN patients with CKD stages prevalence of hyperuricemia in SLE patients is reported to be approximately 16.1% [12] and 29% [13].…”
Section: Introductionmentioning
confidence: 99%
“…Because early intervention on LN improves long-term survival and kidney damage [11], it is important to predict renal damage early. The prevalence of hyperuricemia in SLE patients is reported to be approximately 16.1% [12] and 29% [13]. In LN patients with CKD stages prevalence of hyperuricemia in SLE patients is reported to be approximately 16.1% [12] and 29% [13].…”
Section: Introductionmentioning
confidence: 99%
“…Serum uric acid levels were investigated in various rheumatic diseases [6][7][8][9][10][11]15]. Choe et al [6] studied SUA levels in RA patients and it's association between inflammatory markers such as ESR and CRP in 23 patients treated with methotrexate (MTX) and 27 patients treated with MTX and leflunomide.…”
Section: Discussionmentioning
confidence: 99%
“…SUA levels with inflammatory markers was not found. Sheikh et al [7] detected hyperuricemia in 16.1% of 204 SLE patients and found that hyperuricemia was associated with the occurrence of stroke, peripheral neuropathy, hypertension, hyperlipidemia, and history of arterial thrombosis. Also, SUA levels were studied in psoriasis patients [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheikh i wsp. wykazali, że hiperurykemia u chorych na SLE była istotnie związana z występowaniem udaru i neuropatii obwodowej, niezależnie od nadciśnienia i hiperlipidemii [58], natomiast Sabio i wsp. udowodnili związek pomiędzy podwyższonymi stężeniami kwasu moczowego, homocysteiny i sztywnością tęt-nic, co może wpływać na szybszy rozwój miażdżycy u tych chorych [59].…”
Section: Kwas Moczowy a Choroby Tkanki łąCznejunclassified